2014
DOI: 10.35680/2372-0247.1025
|View full text |Cite
|
Sign up to set email alerts
|

Hearing the patient voice: Using video intervention/prevention assessment to understand teens with cystic fibrosis

Abstract: This qualitative study asked two questions: 1) How do teens with cystic fibrosis (CF) feel about their treatments; and 2) What factors lead teens to adhere, or not adhere, to treatments. To answer these questions we used an innovative approach (Video Intervention/Prevention Assessment or VIA), to learn about the experiences of teens with CF. We loaned video camcorders to teens with CF and asked them to create visual narratives of their lives. Researchers logged and coded videotapes, identifying themes that aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…A range of qualitative studies, which have mainly used a thematic approach to analysis, and reviews have attempted to understand the factors influencing adherence to treatment in CF for adolescents and adults (Abbott, Havermans, & Hart, ; Arias‐llorente, García, & Martín, ; Foster et al ., ; George et al ., ; Hogan, Bonney, Brien, Karamy, & Aslani, ; Hoo, Boote, Wildman, Campbell, & Gardner, ; Horky, Sherman, Laura, Polvinen, & Rich, ; Lask, ; Macdonald et al ., ; Pakhale et al ., ; Sawicki, Heller, Demars, & Robinson, ). These have tended to find that adherence to treatment is reported to be influenced by the extent of treatment burden, having the time to do treatment, having a routine, forgetting to do treatment, a person's identity, perceptions of control, and social support.…”
Section: Introductionmentioning
confidence: 99%
“…A range of qualitative studies, which have mainly used a thematic approach to analysis, and reviews have attempted to understand the factors influencing adherence to treatment in CF for adolescents and adults (Abbott, Havermans, & Hart, ; Arias‐llorente, García, & Martín, ; Foster et al ., ; George et al ., ; Hogan, Bonney, Brien, Karamy, & Aslani, ; Hoo, Boote, Wildman, Campbell, & Gardner, ; Horky, Sherman, Laura, Polvinen, & Rich, ; Lask, ; Macdonald et al ., ; Pakhale et al ., ; Sawicki, Heller, Demars, & Robinson, ). These have tended to find that adherence to treatment is reported to be influenced by the extent of treatment burden, having the time to do treatment, having a routine, forgetting to do treatment, a person's identity, perceptions of control, and social support.…”
Section: Introductionmentioning
confidence: 99%
“…Forgetting is often cited as a barrier to adherence in both CF (e.g., Abbott et al, 2009; Bregnballe et al, 2011; Dziuban et al, 2010; George et al, 2010; Horky et al, 2014; Kahwati et al, 2016; Modi & Quittner, 2006; O’Toole et al, 2019; Owen & John, 2016; Plummer et al, 2008; Sawicki et al, 2014) and other chronic conditions (Gadkari & McHorney, 2012; Horne et al, 2005; Ingersoll & Cohen, 2008; Mills et al, 2006; Rathbone et al, 2017). We do not claim to have uncovered all the different ways in which forgetting is utilized to account for nonadherence of nebulizer treatments in CF (Morse, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified a number of barriers and facilitators to adherence in the adult and pediatric population with CF, including to nebulizer treatments. Commonly reported barriers to adherence include treatment burden, practical issues such as collecting prescriptions, and lack of time to do treatments; competing goals including a desire to be “normal”; lack of perceived treatment effectiveness and understanding of treatment recommendations; negative feelings about nebulizers or more general anxiety and depression; social and work demands; personal characteristics; current state of health; and forgetting (Abbott, Havermans, & Hart, 2009; Arden, Drabble, O’Cathain, Hutchings, & Wildman, 2019; Arias-Llorente, García, & Martín, 2011; George et al, 2010; Hogan, Bonney, Brien, Karamy, & Aslani, 2015; Horky, Sherman, & Polvinen, 2014; Lask, 1994; Macdonald et al, 2016; Plummer, Costall, & Torry, 2008; Sawicki, Heller, Demars, & Robinson, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations